SISTEM KOORDINASI ANTARA PENYIDIK KEPOLISIAN REPUBLIK INDONESIA DAN KOMISI PEMBERANTASAN KORUPSI DALAM PEMBERANTASAN KORUPSI DI INDONESIA - Dahwir, Ali (Faculty of Law, University of Palembang, 2018)
The coordination system between Police investigators and the Corruption Eradication Commission (CEC) against corruption eradication efforts in Indonesia is CEC coordinate the process of investigation, investigation and prosecution of corruption. In this case, the prosecution of all corruption by police should be under the coordination of CEC. In the context of coordinating the prosecution process, the CEC is authorized to request information on all criminal acts of corruption to the police agency. Moreover, if the action is taken against corruption as regulated in Article 11 of the Corruption Eradication Commission Law.